A MOP Based DSL for Testing Java Programs using OCL - Clark, Tony (Electronic Communications of the EASST, 2010)
OCL is used to specify systems by defining pre and post-conditions forclass operations. Typically, the conditions refer to properties and operations that aredefined in a model. When the model is implemented, various implementation decisionsare made regarding properties and operations that cause the OCL conditions tobe inconsistent with the implementation. This paper defines a domain specific language(DSL) for testing and shows how a meta-object-protocol for OCL can be usedto dynamically run tests written in the DSL against different Java implementationsof the same model.